Committee 'A' on Draft Third Five Year Plan (Policy, Resources and Allocations) Synopsis of Proceedings (10th, 11th, 12th and 13th November, 1960) - Planning Commission (Planning Commission, 1960)
The Committee ‘A’ on Policy, Resources and Allocations, of which I had the honour to be the Chairman, met on 10th November and continued its discussions till 1 p.m. on 13th. It held four morning sittings from 9 a.m. to 1 p.m. and three evening sittings from 3 p.m. to 6 p.m. The discussion was conducted in two stages. The first three sittings were devoted to discussion on Policy. In the next three sittings, Resources and Allocations were discussed together. In the last sitting on the 13th morning, Hon. Shri G. L. Nanda, Minister for Planning and Deputy Chairman for Planning Commission, replied to many points raised by the Members in the debates and-finally answered questions put by them. During the debate, many Members were anxious to be assured that the discussions in the Committee should be given a careful consideration by the Planning Commission in framing the final draft of the Plan. Some of them felt that unless the results of the discussions were embodied in a report containing specific recommendations, the speeches of the Members might not have much effect. It was, however, pointed out that it would not be possible to put forward specific recommendations on behalf of the Committee unless they were reduced to specific proposals clothed in precise language and voted upon. However, I undertook to put in a note containing the most important observations and suggestions on which there was a large measure of agreement. This note is being prepared in accordance with that undertaking. I should, however, make it clear that for the selection of points and suggestions and their arrangement, I am solely responsible. It is earnestly hoped that they will be carefully considered by the Planning Commission and attempts will be made to clear the doubts and adopt the suggestions as far as possible.
Lok Sabha Secretariat New Delhi
Lok Sabha Secretariat New Delhi